The optimization of acid hydrolysis on bioethanol production from durian peel waste (Durio zibethinus murr) - Shanta Noventhya Ginting; Epi Kristina Simanullang; Lindu Parningotan Simanullang; Bajoka Nainggolan; Saronom Silaban (Pascasarjana Universitas Negeri Medan, 2018)
Abstract: The dependence on fossil fuels is a big problem and needs an urgent solution. One of the steps taken is the utilization of bioethanol